Sistem Informasi Distributor dan Agen Top Up Berbasis Web Dengan Fitur Payment Gateway Dengan Metode User Centered Design (UCD) - Darmawan Mega Permana; Ilivia; Mulyadi Tan; Jajang Nurjaman; Imron Nugraha; Slamet Santoso; Lisken Sirait (LPPM STMIK Bandung, 2024)
The rapid advancement of technology has heightened the demand for effective information systems, exemplified by web- based distributor and agent top-up systems. This research employs the User Centered Design (UCD) method to ensure that the system development meets user needs, focusing on usability, effectiveness, and satisfaction. Emphasizing the creation of a web-based distributor and agent top-up system with a payment gateway feature, this study engages users from needs analysis to testing. The application of UCD is expected to enhance user satisfaction, streamline top-up transactions, and facilitate payments. The proposed thesis title is